Temperature dependent local phase transformation in shape memory alloys by nanoindentation. (May 2015) - Sgambitterra, Emanuele; Maletta, Carmine; Furgiuele, Franco
Abstract : A novel approach, based on nanoindentation experiments, for analysing temperature dependent local phase transformations in shape memory alloys is proposed. The method was used to analyse cracked specimens and the effects of temperature on local crack-tip transformations were analysed by isothermal nanoindentation tests. Furthermore, experimental results were compared with predictions of a recent analytical model and good agreements were observed. It was demonstrated that the proposed approach can be advantageously used instead of more complex microstructural investigations, like X-ray microdiffraction.